EFEKTIVITAS PERAN DINAS KOPERASI DAN UMKM KOTA PADANG DALAM PENGEMBANGAN USAHA KECIL DAN MENENGAH DI KELURAHAN PURUS KOTA PADANG - Fauziah Fauziah; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research was conducted at the Department of Cooperatives and UMKM in Padang City. It aims to describe the effectiveness of the role of the Padang City Cooperative and UMKM Service in Small and Medium Enterprise Development in Purus Village, Padang City. The effectiveness of the role has several problems that arise, causing the effectiveness of the role to be disrupted and less than optimal for the Padang City Cooperative and UMKM Office. The problem of role effectiveness continues to increase so that more attention is needed by the Padang City Cooperative and UMKM Office in the effectiveness of its role. This studied use a qualitative methods and descriptive approaches which aims to describe, record, explain, interpret (describe) and describe the effectiveness of the role of the Padang City Cooperative and UMKM Service in Small and Medium Business Development in Purus Village, Padang City. The selection of informants are determined by thecnique purposive sampling.. The types of data are primary and secondary data collected through observation, interviews and documentation study. The data analysis techniques used can be grouped into 3 stages, namely data reduction, data presentation and drawing conclusions.He point of view of this studied is the Implementation of the role of the Padang City Cooperative and UMKM Service in Small and Medium Business Development in Purus Village, Padang City has been effective and well implemented, but has not been in accordance with what is expected of UMKM actors to be given marketing and packaging training for UMKM players. In implementing its role it is less effective due to a lack of budget for developing UMKM in Purus sub-district and not all UMKM get assistance with facilities and infrastructure. External constraints on the Effectiveness of the Role of the Padang City Cooperative and UMKM Service in UMKM Development In Purus Village, Padang City is disturbed by the Covid-19 pandemic which hinders the Role of the Padang City Cooperative and UMKM Office in the Development of UMKM in Purus Village, Padang City.